Cluster Country Program Evaluation on Small States : Pacific Island Countries Program Evaluation (FY05–15) - Independent Evaluation Group (World Bank, Washington, DC, 2021)
This appendix is an adjunct to the main report. It is not intended as a free-standing Country Program Evaluation (CPE) on the World Bank in Tonga. It provides additional underpinning and evidence for the overall story of the Bank’s relevance and effectiveness in the PICs provided in the main report. The Tonga country assistance strategy (CAS) was prepared in 2010 and covered the period from FY11 to FY14. The CAS signaled a considerable scaling up of analytic and financial support for Tonga (and the other PICs). It identified connectivity as the Bank’s major contribution over the previous five years, through the support for increased temporary migration opportunities and the encouragement of telecoms reform that led to the opening of the market for mobile telephones. In addition to the two broad themes in the regional framework (connectivity and resilience), the CAS added a third: Supporting policy reform to strengthen growth prospects and improve service delivery. Going forward the Bank planned to make increased use of the development policy operation (DPO) instrument which would support Tonga during the very difficult period it was going through at the time, given the combination of coping with the global crisis and with natural disasters. There was to be emphasis on support for improved governance and public financial management (PFM) reforms. Under the theme of Building resilience against shocks, the Bank looked to tap the Global Facility for Disaster Reduction and Recovery (GFDRR) to provide support for integrated adaptation and disaster risk management (DRM) activities. The GFDRR would also be used to “climate proof” future infrastructure investment. The CAS also declares the intention in small island states like Tonga to be, more nimble in project preparation and give greater attention to implementation support. The Bank can at times be more of an elephant than a lynx.